2000
DOI: 10.1007/s002130000521
|View full text |Cite
|
Sign up to set email alerts
|

Association between the serotonin 2C receptor gene and tardive dyskinesia in chronic schizophrenia: additive contribution of 5-HT2C ser and DRD3 gly alleles to susceptibility

Abstract: These findings support a small but significant contribution of the HT2CR and DRD3 to susceptibility to TD, which is additive in nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
2
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(83 citation statements)
references
References 23 publications
4
75
2
2
Order By: Relevance
“…Studies on 5-HT6 and 5-HTT polymorphisms failed to find any association. 205,251,252 Further studies investigating 5-HT 2C , 5-HT 2A and D 3 genotypes with age and disease phenotypes 249,250 provided significant associations confirming the involvement of dopamine and serotonin systems in susceptibility to TD.…”
Section: Prediction Of Side Effectsmentioning
confidence: 76%
“…Studies on 5-HT6 and 5-HTT polymorphisms failed to find any association. 205,251,252 Further studies investigating 5-HT 2C , 5-HT 2A and D 3 genotypes with age and disease phenotypes 249,250 provided significant associations confirming the involvement of dopamine and serotonin systems in susceptibility to TD.…”
Section: Prediction Of Side Effectsmentioning
confidence: 76%
“…61 By using stepwise multiple regression analyses, the inclusion of DRD3 genotypes revealed an additive contribution of the 5-HT2C Ser allele and the DRD3 Gly allele, respectively, of 4.2 and 4.7% to the variance of orofacial dyskinesia (OFD) scores in the overall sample. 61 Zhang et al 62 found a significant association (including only males) with the 5-HT2C promoter variant À697C allele, but not with the À759C/T variants or with haplotype analyses. No association has been reported between the 5-HT6 receptor, or the serotonin transporter 59,63 and TD.…”
Section: The Serotonergic Systemmentioning
confidence: 99%
“…Only recently have studies begun to investigate the additive or interactive effects among different risk alleles. 37,61,83 . In our sample, the risk alleles of the DRD3 and CYP1A2 genes were found to be highly associated with TD (P ¼ 0.00007) in an additive, co-recessive model of interaction which accounted for 450% of the variance in risk for TD.…”
Section: Outlook: Clinical Implicationsmentioning
confidence: 99%
“…An intriguing study reported that the nonsynonymous substitution of G by C at position 68 of the 5HT2C gene (leading to a cys23ser conversion) additively contributed to increase TD susceptibility in individuals carrying gly9 DRD3. 24 We analyzed the 5HT2C gene in C. apella and found that all monkeys were homozygous for the cys23 allele. This finding suggests that high TD susceptibility can be present in a species in the absence of the serine version of the 5HT2C receptor and without the possible additive contribution of gly9 DRD3 and ser23 5HT2C reported in humans.…”
Section: T Werge Et Almentioning
confidence: 99%
“…Also, we have examined the 5HT2C gene in C. apella and determined the sequence around position +68, which has been shown to be polymorphic and potentially associated with TD in humans. 24 …”
Section: Introductionmentioning
confidence: 99%